Do Stress Trajectories Predict Mortality in Older Men? Longitudinal Findings from the VA Normative Aging Study. (29th June 2011) - Aldwin, Carolyn M.; Molitor, Nuoo-Ting; Spiro, Avron; Levenson, Michael R.; Molitor, John; Igarashi, Heidi
Abstract : We examined long-term patterns of stressful life events (SLE) and their impact on mortality contrasting two theoretical models: allostatic load (linear relationship) and hormesis (inverted U relationship) in 1443 NAS men (aged 41–87 in 1985; M = 60.30, SD = 7.3) with at least two reports of SLEs over 18 years (total observations = 7, 634). Using a zero-inflated Poisson growth mixture model, we identified four patterns of SLE trajectories, three showing linear decreases over time with low, medium, and high intercepts, respectively, and one an inverted U, peaking at age 70. Repeating the analysis omitting two health-related SLEs yielded only the first three linear patterns. Compared to the low-stress group, both the moderate and the high-stress groups showed excess mortality, controlling for demographics and health behavior habits, HRs = 1.42 and 1.37, p s< .01 and< .05 . The relationship between stress trajectories and mortality was complex and not easily explained by either theoretical model.